Epizootic Landscapes: Sheep Scab and Regional Environment in England in 1279–1280. (2nd July 2016) - Slavin, Philip
ABSTRACT: This essay looks at late-medieval rural landscapes of animal disease through the prism of sheep epizootics in England, caused by sheep scab, a highly acute and transmissive disease, whose first wave broke out in 1279–1280. The essay focuses on three regions in England: East Anglia, the Wiltshire-Hampshire Chalklands and Kent, each possessing distinct topographic and environmental features and exhibiting different rates of mortality. The study sets a theoretical model, based on the concept of 'complexity theory' and consisting of ten different principles, determining regional variances in dissemination of scab and in mortality patterns. A close analysis of the available statistical sources suggests that there was no 'universal' explanatory factor accounting for the correlation between regional geography and mortality rates, and that the situation varied not only from region to region, but from farm to farm, depending on a combination of several possible factors. It is only through a meticulous analysis of local, rather than regional, conditions that the complexity of the situation can begin to be appreciated